A CONCEPTUAL REVIEW OF JALAUKAVACHARANA - Bhardwaj, Richa; Tanwar, Ankur Kumar; Gupta, H.C. (International Journal of Ayurveda and Pharma Research, 2019)
The basic Ayurvedic treatment is based on two principles viz. Shodhan chikitsa (elimination Therapy) and Shaman chikitsa (internal medicine). Shodhan Chikitsa deals with five purificatory procedures popularly known as Panchakarma. Acharya Susruta included Raktamokshana in Panchakarma and described it as the best procedure because it eliminates all three vitiated Doshas viz. Vata, Pitta & Kapha. Jalaukavacharana is a type of Raktamokshana where leeches are used for bloodletting. This is considered as the most effective and most unique method of Raktamokshana as vitiated Doshas are removed from the body without using any cutting instruments, so, Raktamokshana by means of ‘Leech’ comes under Ashastra category. The following paper deals with the basic concepts of Leech therapy and the method of using leech for Raktamokshana.